The cost-effectiveness analysis of serplulimab versus regorafenib for treating previously treated unresectable or metastatic microsatellite instability-high or deficient mismatch repair colorectal cancer in China - Ma, Yue; Zhou, Jiting; Ye, Yuxin; Wang, Xintian; Ma, Aixia; Li, Hongchao (Frontiers in Oncology, 2023)
Objective The aim of this study was to investigate the cost-effectiveness of serplulimab versus regorafenib in previously treated unresectable or metastatic microsatellite instability-high (MSI-H) / deficient mismatch repair (dMMR) colorectal cancer in China. Methods From the perspective of China’s health-care system, a Markov model with three health states (progression free, progression, death) was developed for estimating the costs and health outcomes of serplulimab and regorafenib. Data for unanchored matching-adjusted indirect comparison (MAIC), standard parametric survival analysis, the mixed cure model, and transition probabilities calculation were obtained from clinical trials (ASTRUM-010 and CONCUR). Health-care resource utilization and costs were derived from government-published data and expert interviews. Utilities used to calculate quality-adjusted life years (QALYs) were obtained from clinical trials and literature reviews. The primary outcome was the incremental cost-effectiveness ratio (ICER) expressed as cost/QALY gained. Four scenarios were considered in scenario analysis: (a) using original survival data without conducting MAIC; (b) limiting the time horizon to the follow-up time of the clinical trial of serplulimab; (c) adopting a fourfold increase in the risk of death; and (d) applying utilities from two other sources. One-way sensitivity analysis and probabilistic sensitivity analysis were also performed to assess the uncertainty of the results. Results In the base-case analysis, serplulimab provided 6.00 QALYs at a cost of 68,722, whereas regorafenib provided 0.69 QALYs at a cost of 40,106. Compared with that for treatment with regorafenib, the ICER for treatment with serplulimab was 5,386/QALY, which was significantly lower than the triple GDP per capita of China in 2021 (30,036), which was the threshold used to define the cost-effectiveness. In the scenario analysis, the ICERs were 6,369/QALY, 20,613/QALY, 6,037/QALY, 4,783/QALY, and 6,167/QALY, respectively. In the probabilistic sensitivity analysis, the probability of serplulimab being cost-effective was 100% at the threshold of 30,036/QALY. Conclusion Compared with regorafenib, serplulimab is a cost-effective treatment for patients with previously treated unresectable or metastatic MSI-H/dMMR colorectal cancer in China.